Youth and Socialization Spaces: A Field Study on Prediction of Risky Alcohol Use by Need for Social Approval and Drinking Motives in Alcohol-Using University Students - Demet Atlam; Deniz Tan; Selen Açıkyol (Addicta: The Turkish Journal on Addictions)
University students’ alcohol use is greatly influenced by socialization places. The aim of the study is to examine the factors leading to risky alcohol use and evaluate the role of need for social approval and drink- ing motives. The cross-sectional study was conducted as field research in campus cafes and “Küçükpark” in May–July 2024. 429 university students who were using alcohol were evaluated using the Addiction Profile Index Risk Screening-Alcohol, Drinking Motives Questionnaire-Revised, and Need for Social Approval Scale. Pearson chi-square, independent sample t test, analysis of variance, correlation test, and binary logis- tic regression tests were used. Risky alcohol use was explained by drinking motives, daily–weekly alcohol use, drinking alone, smoking characteristics, consumption alcohol with energy drinks, alcohol use in the family environment, and the presence of alcohol addiction in friends, partners, and family. Need for social approval was not correlated with risky alcohol use but was correlated with conformity of drinking motives. As a result, alcohol is becoming an integral component of socializing in university life. Young individuals prefer to consume alcohol by adapting to groups to be accepted and satisfy their social approval needs, but this does not reach the level of risky alcohol use.